Enhancing Strategic Management for Resilient Supply Chains in Construction Industry 4.0: A Fuzzy EDAS Methodology - Faghidian, Seyede Fatemeh; Moradi, Behnam (Risk Assessment and Management Decisions, 2025)
Strategic management of one of the most complex and profitable supply chains necessitates the creation of transient and repeatable competitive advantages. The escalating disruptions in such supply chains underscore the criticality of resilience strategies for construction firms. By simultaneously considering all influencing variables, three primary criteria, human capital, technological development, and supply chain capabilities, along with fourteen sub-criteria, were identified. To prioritize these under the ambiguous and uncertain conditions of the real world, the Fuzzy EDAS technique was employed. The results highlight the primacy of human resources over technology, despite the latter being a hallmark of Industry 4.0. This intriguing paradox underscores the pivotal role of managers and employees, and their capabilities, in fostering supply chain resilience, followed by the integration of Industry 4.0 technologies.